Multidisciplinary management of a complex abdominal wound post necrotising fasciitis: a case study. (2nd November 2022) - Wynn, Matthew; Gibson, Ruth; Goldsmith, Paul
Abstract : A 59-year-old male patient presented with abdominal necrotising fasciitis secondary to a bowel perforation through a previous drain site that he had waited at home with for two weeks. Enteric contents were found within the abdominal wall. Surgery required extensive abdominal wall debridement and the formation of a double-barrel ileostomy within the debrided area. The resulting abdominal wound was large, initially covering an area of approximately 424cm 2, and had continuous contamination from enteric leakage that could not be isolated. Achieving wound healing was challenging due to the enteric output and resultant continuous contamination of the wound bed.